2014
DOI: 10.1590/abd1806-4841.20142930
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome and its components in a Brazilian sample of pemphigus patients

Abstract: BACKGROUNDPemphigus foliaceus and pemphigus vulgaris are endemic in the northeastern region of São Paulo State, Brazil. They are treated mainly with systemic corticosteroids, which may provoke osteoporosis; atherosclerosis, higher blood pressure, insulin resistance, glucose intolerance, hyperlipidemia and abdominal obesity. These side effects of corticoids also constitute criteria for the diagnosis of metabolic syndrome.OBJECTIVEThe prevalence of metabolic syndrome and each component of metabolic syndrome in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
2
15
0
2
Order By: Relevance
“…However, the increased incidence of PV and PF in individuals with metabolic conditions was reported here. A previous Brazilian study showed that patients with pemphigus had an increased risk of metabolic syndrome because of steroid treatment of pemphigus . In our study, the incidence of PV and PF was increased in individuals with hypertension, dyslipidemia and diabetes mellitus.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, the increased incidence of PV and PF in individuals with metabolic conditions was reported here. A previous Brazilian study showed that patients with pemphigus had an increased risk of metabolic syndrome because of steroid treatment of pemphigus . In our study, the incidence of PV and PF was increased in individuals with hypertension, dyslipidemia and diabetes mellitus.…”
Section: Discussionsupporting
confidence: 66%
“…A previous Brazilian study showed that patients with pemphigus had an increased risk of metabolic syndrome because of steroid treatment of pemphigus. 36 In our study, the incidence of PV and PF was increased in individuals with hypertension, dyslipidemia and diabetes mellitus. Considering that the side-effects of glucocorticoids include osteoporosis, atherosclerosis, increased blood pressure, insulin resistance, glucose intolerance, hyperlipidemia and central obesity, the importance of comorbid metabolic diseases in PF and PV individuals should be emphasized.…”
Section: Discussionsupporting
confidence: 49%
“…Cardiovascular disease has recently been shown to be associated with pemphigus . Excess cardiovascular risk may be due to chronic inflammation, decreased physical activity secondary to itch and pain, as found in other inflammatory skin disorders, or use of systemic corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Identification and management of the comorbidities of pemphigus are critically important to decrease disease‐associated morbidity and mortality. In various cohort studies and case reports, pemphigus has been associated with cardiovascular diseases such as type 2 diabetes mellitus and hyperlipidaemia; infections; various autoimmune diseases, such as autoimmune thyroiditis and the inflammatory bowel diseases; side‐effects from long‐term steroid use such as decreased bone mineral density and adrenal insufficiency; and malignancies and psychiatric comorbidities . Many of these studies had conflicting results about certain comorbidities and were limited by small sample sizes, which resulted in insufficient statistical power.…”
mentioning
confidence: 99%
“…Dear Editor , Previous studies have explored the epidemiology of autoimmune blistering disease (AIBD), but all have been limited to single centres with cohorts that typically have at most a few 100 patients . In order to truly understand the epidemiology of AIBD, evaluation of large‐scale datasets that are representative of the broader population is needed.…”
Section: Co‐occurrence Of International Classification Of Diseases 9tmentioning
confidence: 99%